Personal and Environmental Influences on Smoke-Free AreaCompliance : a Literature review - Eka Rachmawati; Annisa Nurrachmawati; Nur Rohmah (Mulawarman International Conference on Tropical Public Health, 2025)
The government has established smoke-free policies, but despite the issuance of various regulations, the implementation of smoke-free areas in the field still faces serious challenges, one of which is low public compliance. Factors that influence compliance include personal factors and environmental factors. Objective : The purpose of this study is to conduct a literature review of studies that investigate the influence of personal factors and environmental factors on compliance with no-smoking areas in public facilities. Research Methods/ Implementation Methods : The research method used in this study is a Systematic Literature Review (SLR) using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses). Search from Google Scholar, PubMed, and Research Gate, using the keywords "kepatuhan" (compliance), "smoke free area", and "kawasan tanpa rokok" (smoke-free zone) Results : Articles published from 2017 to 2025. From the 225 articles identified, 10 articles were selected for use after applying inclusion and exclusion criteria. Conclusion/Lesson Learned : personal factors (knowledge, attitude, self-efficacy, perception) and environmental factors (quality of smoking facilities, no smoking signs) influence compliance with the implementation of smoke-free areas in public facilities. These two factors are integrated and interact reciprocally (reciprocal determinism).